Assessment of Competencies of Districts’ Surveillance Officers in Iraq - Mahmood , Rafal R.; Al-Safi, Aliaa M.; Al-Lami, Faris Hasan (AL-Kindy College Medical Journal, 2024)
Background: Assessment of communicable diseases surveillance officers is one of the important aspects of the detection of obstacles that prevent the development of surveillance system, which would certainly affect their control programs.Objectives:  To assess the Competencies of communicable diseases' surveillance officers in all Iraqi provincesSubjects and Methods: A cross sectional study from the15th March to 30th September 2019 in which all the communicable diseases' surveillance officers (136) that are employed by Ministry of Health all over Iraq were included. A structured questionnaire developed by the researcher and filled by them. The questionnaire form gathered demographic data, service characteristics and status of competencies including basic epidemiology, biostatistics, surveillance, outbreak investigation, rapid response to health incidence and developing scientific reports.Results: The response rate was 85.3%, about half of surveillance officers was responsible for less than 10 Primary Health Care Centre. More than half of them (55.3%) were responsible for 1-2 hospitals. Their age ranged between 21 and 62 years and the males constituted more than three quarters (78.4%) of the study sample, Diploma was the highest educational certificate. 15.6% of the sample did not attend any training activity. Cholera has been the most frequently reported incident (53.8%).Conclusions: The surveillance system in Iraq at district level was operated mainly by low qualified and under-trained health personnel. There is inequity in distribution of workload and training sessions between surveillance officers in health offices, therefore redistribution is recommended. Supporting continuous training programs with increase incentives.